2020
DOI: 10.1177/0960327120909530
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin (S100A8/S100A9)-induced cytotoxicity and apoptosis in human gastric cancer AGS cells: Alteration in expression levels of Bax, Bcl-2, and ERK2

Abstract: Calprotectin is a heterodimeric EF-hand Ca2+ binding protein that is typically released by infiltrating polymorphonuclear leukocytes and macrophages. This protein is a key player linking inflammation and cancer. Due to the increased levels of calprotectin in different inflammatory diseases and cancer, it is considered as a marker for diagnostic purposes. In this study, we evaluated the mechanism of cell viability and apoptotic-inducing effects of recombinant human calprotectin (rhS100A8/S100A9) on the gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…We conducted a literature review on DEmRNAs in the PPI submodules of the three lesion stages (Tables S1–S5, Supporting Information [ 15–42 ] ). All the DEmRNAs were confirmed to be associated with cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a literature review on DEmRNAs in the PPI submodules of the three lesion stages (Tables S1–S5, Supporting Information [ 15–42 ] ). All the DEmRNAs were confirmed to be associated with cancers.…”
Section: Resultsmentioning
confidence: 99%
“…All the DEmRNAs were confirmed to be associated with cancers. A significant association was found between DEmRNAs in module 1 of LGIN (three of six DEmRNAs [15][16][17] ), module 2 of LGIN (eight of nine DEmRNAs [21,24,26] ), and module 3 of LGIN (three of four DEmRNAs [27,29] ), as well as module 1 of HGIN (all DEmRNAs [21,22] ), module 2 of HGIN (three of four DEmRNAs [31,32,34] ), and module of EGC (seven of nine DEmRNAs [27,29,35,41,42] ), with the progression, invasion, or prognosis of GC. In this study, some new DEmRNAs were found in the LGIN, HGIN, and EGC stages, including SLC51A, A1CF, TM4SF4, ORM2, and KRT14 in LGIN stage, MMP3 in HGIN stage, and MMP3, FCGR3A, and MNDA in EGC stage.…”
Section: Identified Ppi Submodules Of Three Lesion Stagesmentioning
confidence: 99%
“…Regarding specific proteins, in nonsusceptible individuals, we observed higher expression in general of the S100 proteins (calprotectin) family, which are calcium- and zinc-binding proteins produced by immune cells and involved in several cellular processes, including cycle progression and differentiation, immune regulation, inflammation, etc. [ 48 , 69 , 70 ]. Increased expression of S100A6 is related to signal transduction, ion transmembrane transport, positive regulation of fibroblast proliferation, or protein binding [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular signal regulated kinase (ERK), a mitogen activated protein of the white kinase (MAPK) family, mediates the intracellular transduction of various signals [ 21 , 22 ]. Elevated phosphorylation of this protein has been reported in different pain models.…”
Section: Discussionmentioning
confidence: 99%